Pengaruh Diabetes Mellitus Terhadap Kejadian Disfungsi Ereksi - Alpacino J. Wowor; Lydia E. N. Tendean; Janette M. Rumbajan (Universitas Sam Ratulangi, 2021)
Abstract: Diabetes Mellitus (DM) is a non-communicable disease that can be found at all ages, especially in adults and the elderly. Erectile Dysfunction (ED) is the inability to maintain an erection. Like DM, DE is still a problem facing the world, including Indonesia. Blood vessels can be damaged by various factors, one of which is uncontrolled blood sugar levels that can lead to Erectile Dysfunction. The International Index of Erectile Function (IIEF-5) or Sexual Health Inventory for Men (SHIM) is a tool for diagnosing ED. The purpose of this study was to determine the effect of Diabetes Mellitus on the incidence of Erectile Dysfunction. This study took the form of a literature review with data searches using three databases, namely Pubmed, ScienceDirect and Google Scholar. The keywords used were Diabetes Mellitus